Kearifan Lokal Alas Duwe sebagai Sumber Belajar Konservasi Hutan pada Masyarakat Bali - Gusti Ayu Dewi Setiawati; Ni Nyoman Tri Wahyuni (Sphatika: Jurnal Teologi, 2022)
The function of the forest is very important. Apart from being a source of storage and regulation of water, forests have other functions, namely sources of plant and animal germplasm, soil reserves, energy sources, sources of production materials and human needs, and aspects of the biosphere that cannot be replaced. The importance function of the forest causes the forest to never escape from its use and management, and efforts are always made to maintain its sustainability. Behind the rampant forest destruction, in Bali there are several forest areas that are still being preserved, known as alas duwe. This study aims to describe alas duwe as a form of local wisdom of the Balinese people. The study used a qualitative approach with data collection in the form of journal documentation, articles and books, data analysis is used through stages, including; data reduction, data presentation, triangulation and drawing conclusions. Based on the study, it was found that the existence of alas duwe is a social control mechanism that controls the behavior of the surrounding community, thus enabling alas duwe to remain sustainable. Local wisdom in the form of forests in Bali can be used as a learning source.